2021
DOI: 10.3389/fmars.2021.770722
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Catch Rate Characteristics of Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in Relation to Oceanographic Factors in the Waters Around Taiwan

Abstract: This study investigated the relationship of the catch rates (CRs) of Spanish mackerel (Scomberomorus commerson) with oceanographic factors in the waters around Taiwan by using high-resolution fishery and environmental data for the period 2011–2016. The investigation results revealed that trammel nets accounted for 69.79% of the total catch of S. commerson and were operated mostly in the Taiwan Strait (TS). We noted seasonal variations in the distribution of high CRs. These CRs were observed in the southwestern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bathymetric surveys conducted in the coastal waters of Taiwan have revealed that the average water depth in the western coastal areas (<50 m) is lower than that in the eastern coastal areas (>2000 m) [69]. Water depth is a key oceanographic feature that influences the shape and structure of marine species communities.…”
Section: Environmental Factors Affecting the Greater Amberjackmentioning
confidence: 99%
“…Bathymetric surveys conducted in the coastal waters of Taiwan have revealed that the average water depth in the western coastal areas (<50 m) is lower than that in the eastern coastal areas (>2000 m) [69]. Water depth is a key oceanographic feature that influences the shape and structure of marine species communities.…”
Section: Environmental Factors Affecting the Greater Amberjackmentioning
confidence: 99%
“…Kuroshio, and Coastal China Sea currents, may affect the movement of the greater amberjack in the TS when seasonal changes occur, leading to a wide distribution of the species. Previous research on various marine fish species in the TS has shown that the catch rates and spatial distribution patterns are influenced by seasonal changes in physical processes of various currents and climate-related environmental variability (Lan et al, 2014;Chen et al, 2021).…”
Section: Seasonal Catch Rate Variations and Spatial Distribution Patt...mentioning
confidence: 99%